The benefit of kitchen exhaust fan use after cooking - An experimental assessment. (1st May 2018) - Dobbin, Nina A.; Sun, Liu; Wallace, Lance; Kulka, Ryan; You, Hongyu; Shin, Tim; Aubin, Daniel; St-Jean, Melissa; Singer, Brett C.
Abstract: Cooking is one of the main sources of indoor air pollutants, and may even exceed the contribution from outdoor sources. This pilot study examines the use of different flow-rate fans during cooking and tests whether continuing to run the fan after cooking significantly improves pollutant removal rates and integrated exposures. Tests were carried out in the Canadian Centre for Housing Technology's twin research houses, in Ottawa, Ontario. We completed the same cooking protocol 60 times on a gas stove, testing 6 different flow rates on three different over-the-range exhaust fans, while continuously measuring UFP, PM2.5, NO2, and NO. The fan was operated during cooking for all tests and then either turned off or left on after cooking for the duration of the three hour test. We estimated decay rates, source emission rates, and integrated exposures to measured pollutants following the cooking test. The results showed that while leaving the fan on after cooking generally increased decay rates, it had a relatively small effect on integrated exposures compared to the effects of fan flow rate and the specific fan used during cooking. For PM2.5, the effect of running an exhaust fan for 15 min after cooking was similar in magnitude to the impact of a 100 cfm increase in the flow rate used while cooking: both were associated with a decrease in 15-min integrated exposure of roughly 3 μg m −3 . This suggests that one can partially compensate for a low flow rate exhaust fan by continuing to run the fan after cooking. Highlights: First study to examine the impact of continuing to use a kitchen exhaust fan after cooking. Experiments conducted in controlled but realistic test homes. Flow rate of fan during cooking was the main determinant of pollutant concentration. 15 min of additional fan use reduced integrated exposure to UFP and PM2.5. Reductions were similar in magnitude to the impact of a 100cfm increase in fan flow rate.